KEBIJAKAN PEMERINTAH HINDIA BELANDA MENGENAI PENDIDIKAN BAGI KAUM BANGSAWAN DI INDONESIA TAHUN 1900-1920 - Widi Indah; Maskun Maskun; Syaiful M (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2013)
Dutch East Inies Government ability regarding education for the count in Indonesia in 1900-1920. This research aims to know state of the implementation of the Dutch East Indies government ability in the field of education for the nobility in Indonesia in 1900-1920. The method is the historical research methods. The method is the historical research methods. The collection data technique used documentation an literation study, while the analysis of the data used is analysis of qualitative data. The results showed that the Dutch East indies government’s education policy is given to the Indonesian people are preferred for the nobility Bumiputera. Dutch East Indies government policy of education for the nobility in Indonesia is in the form of the estabilishment of school institution. School that established by the Ducth government for the nobility in Indonesia, among which: ELS (Europese Lagere School) an elementary school Europe , HBS (Hogere Burger School)is a high school , HIS (Hollandse Inlandse School) an elementary school for the children of the people honored Bumiputera, dan OSVIA ( Opleiding School Voor Inlandsche Ambteneren) an elementary school.Key word : Ability, education and nobility